Minimum Wage as Foundation for Dignified Life in the EU - Zuzana Mackova (Bulletin of the Transilvania University of Braşov: Series VII: Social Sciences, Law)
The COVID 19 pandemic has disclosed various pockets of low level of social protection of the EU parts of populations working for the minimum or even sub-minimum salary. This concerned mainly workers and employees in public health-care, education, social and care services as well as the service sector – such as retail, repair, hospitality, trade and small enterprise. The issue of differences in the level of the minimum salary in various member states of the EU has repeatedly come to the fore, posing a question of adequacy of the minimum salary or wage able to secure a life of human dignity across the EU.